2020
DOI: 10.7150/thno.40687
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent imaging of vascularization and metabolism in a mouse model of paraganglioma under anti-angiogenic treatment

Abstract: Rationale: Deregulation of metabolism and induction of vascularization are major hallmarks of cancer. Using a new multimodal preclinical imaging instrument, we explored a sequence of events leading to sunitinib-induced resistance in a murine model of paraganglioma (PGL) invalidated for the expression of succinate dehydrogenase subunit B (Sdhb -/-). Methods: Two groups of Sdhb -/-tumors bearing mice were treated with sunitinib (6 weeks) or vehicle (3 weeks). Concurrent Positron Emission Tomography (PET) with 2′… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Our results highlight the contribution of multi-organ/multi-modality in vivo imaging for a theranostics approach as proposed earlier 53 , 54 . Such approaches demonstrate that sunitinib-induced cardiotoxicity has several origins, involving a minima pressure-overload, the endothelin axis, and a third mechanism or pathway that remains to be determined for late cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 79%
“…Our results highlight the contribution of multi-organ/multi-modality in vivo imaging for a theranostics approach as proposed earlier 53 , 54 . Such approaches demonstrate that sunitinib-induced cardiotoxicity has several origins, involving a minima pressure-overload, the endothelin axis, and a third mechanism or pathway that remains to be determined for late cardiac hypertrophy.…”
Section: Discussionsupporting
confidence: 79%
“…Metabolic resistance preceded tumor growth which was evident after four weeks of treatment. This evidence suggests that 18 F-FDG PET could monitor precisely metabolic changes of PGL during an anti-angiogenic treatment and could possibly predict disease progression (60).…”
Section: Discussionmentioning
confidence: 90%
“…The instrument was assembled from an existing pre-clinical PET-CT system and a clinical UUI device, with the addition of a motorized micro-positioner to operate the US probe within the PET/CT field of view. They showed no significant degradation of PET image quality due to the presence of the US probe (Perez-Liva et al, 2018) and demonstrated the feasibility and interest of hybrid PET/CT/UUI for cancer and cardiac multi-parametric 3D imaging in mice and rats (Facchin et al, 2020). They also mentioned the interest of PET and UUI hybridization for functional brain imaging in rodents.…”
Section: Technical Hybridization Of Neuroimaging Techniquesmentioning
confidence: 90%